Shariah supervisory boards of Islamic banks in Bangladesh: expected duties and performed roles and functions - Alam, Md. Kausar; Ab Rahman, Suhaimi; Tabash, Mosab I.; Thakur, Oli Ahad; Hosen, Sharif (Emerald Publishing Limited, 2021)
Purpose The main aim of this research is to ascertain the expected duties and performed roles and functions of the Shariah supervisory boards (SSBs) of Islamic banks in Bangladesh. Design/methodology/approach A semi structured face-to-face interview was applied to accomplish the research objectives. In total, data was collected from 17 respondents with a combination of regulators, SSBs, Shariah department executives and experts from the central bank and Islamic banks in Bangladesh. Findings This study finds that the expectations of Islamic banks toward SSB members are to provide opinions on Shariah issues, guidelines and decisions regarding the modern banking, practices and delivering of fatwas on the contemporary issues offered by the management to fulfil the demand of the numerous stakeholders. In addition, they can develop Shariah governance (SG) policies and implement those guidelines, approve and develop new products, observe and monitor banking functions, identify problems and outline solutions as well as they should ensure Shariah principles and compliance. The SSBs members perform roles and functions in monitoring and reviewing overall banking activities and functions; reviewing products, services and contracts; preparing SG guidelines; ensuring Shariah principles and compliance; providing opinions on existing SG practices and finally, delivering Shariah resolutions on the overall functions. Research limitations/implications This study significantly contributed to the national regulatory bodies by providing suggestions that the existing SG system should be improved to enhance the overall monitoring of SSB and ensure more Shariah compliance in the overall operations of the Islamic banks in Bangladesh. Originality/value This is the first research to the best of authors’ knowledge that explores the expected duties and performed roles and functions of the Islamic banks concerning Bangladesh. This study also contributes to the agency, legitimacy and stakeholder theories by outlining the expected and performed roles of SSBs to the Islamic banks and stakeholders.